Exploring Strategies to Optimize the Collection of Zakat on Shares in Indonesia - Sheila Amalia (Institute for Research and Community Empowerment (LPPM TAZKIA), 2018)
This research aims to analyze the priorities of the problems in the collection of zakat on shares, and then identify the best solutions and strategies to enhance the collection performance. The employed method is Analytic Network Process (ANP). The result shows that there are three main problems in collecting zakat on shares: (1) The absence of government enforcement, (2) No integrated services to the zakat institutions (OPZ), and (3) The less understanding of investors about zakat on shares. As for the solutions by priority are: (1) Providing integrated services to the OPZ, (2) Make a collaboration to the securities, and (3) To increase the awareness to pay out zakat on shares. Meanwhile, the best strategies by priority are (1) Regulatory approach from Indonesian Stock Exchange to securities, (2) Zakat payroll system on shares, and (3) Campaign in the television.